2015
DOI: 10.3892/mmr.2015.3308
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and transcription factors associated with glucocorticoid response in lens epithelial cells

Abstract: Prolonged glucocorticoids (GCs) treatment may lead to the formation of posterior subcapsular cataracts. The present study aimed to investigate differential gene expression in lens epithelial cells (LECs) in response to GCs using DNA microarray profiling. The gene expression profile of GSE13040 was downloaded from the Gene Expression Omnibus database, which includes 12 human LECs treated with vehicle or dexamethasone (Dex) for 4 or 16 h with six samples at each time period, of which three samples were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In another study, investigators posited that GCs downregulated expression of CCL2 in lens epithelial cells, suggesting a potential role for CCL2 in GC-induced cataracts [37]. Furthermore, this study also showed that the transcription factor c-Jun binds to the promoter regions of CCL2 to mediate its expression in the pathogenesis of GC-induced cataracts [37]. Hence, we conclude that CCL2 may participate in a variety of biological processes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In another study, investigators posited that GCs downregulated expression of CCL2 in lens epithelial cells, suggesting a potential role for CCL2 in GC-induced cataracts [37]. Furthermore, this study also showed that the transcription factor c-Jun binds to the promoter regions of CCL2 to mediate its expression in the pathogenesis of GC-induced cataracts [37]. Hence, we conclude that CCL2 may participate in a variety of biological processes.…”
Section: Discussionsupporting
confidence: 69%
“…One study indicated that exogenous GILZ inhibits lipopolysaccharide-induced MCP-1 expression in rat retinal vascular endothelial cells through enhancing p65 dephosphorylation [36]. In another study, investigators posited that GCs downregulated expression of CCL2 in lens epithelial cells, suggesting a potential role for CCL2 in GC-induced cataracts [37]. Furthermore, this study also showed that the transcription factor c-Jun binds to the promoter regions of CCL2 to mediate its expression in the pathogenesis of GC-induced cataracts [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the past several years, many studies have claimed that mTOR inhibition affects transcription by regulating the activation of specific transcription factors [27, 44]. Our transcriptomic analysis revealed 3 differentially expressed transcription factors—TCF20, NRL, and NFYB—the expression of which was related to mTORC1.…”
Section: Discussionmentioning
confidence: 78%
“…In vitro studies using human lens epithelial cells (LEC) suggested that GCs affect cell proliferation, differentiation, apoptosis, survival, and migration, through non-genomic modulation of ERK/MAPK pathway [41]. Microarray analysis of LECs revealed multiple genes that were differentially regulated following DEX treatment compared to the control groups including upregulation in monocyte chemotactic protein-1 gene; CCL2 and downregulation of FAS receptor levels, an important cell surface receptor of the tumor necrosis factor receptor family, suggesting a potential role of inflammation in GC-induced cataract [42]. This finding was further supported by another study documenting that CCL2 was detected in patients’ samples following cataract surgery [43].…”
Section: Introductionmentioning
confidence: 99%